The positive background of hindu sociology - Sarkar, Benoy Kumar (Delhi Motilal Banarsidass, 1985)
The work is mainly an analytical study of Sukracharya's code so that the data of hindu sociology collected here reflect generally those phases of Indian cultural evolution which have influenced the authors of the Sukra cycle.